Patient Safety Culture among Nurses in Pokhara Academy of Health Sciences, Nepal - Adhikari, Rita; Khadka, Shanti; Subedi, Babita; Paudel, Kabita; Gurung, Gaura (Journal of Nursing and Health Sciences Nepal, 2025)
Background: Patients’ safety is the absence of preventable harm to a patient and reduction of risk of unnecessary harm associated with health care to an acceptable minimum. Assessing health care professionals’ perception, in patient safety culture plays a crucial role towards initiation of safety culture within organization. The objective of the study was to find out patient safety culture among nurses in Pokhara Academy of Health Sciences, Nepal.Methods: A quantitative descriptive institutional based cross sectional study design was carried out using a self -administered “Hospital Survey on Patients Safety Culture form” developed by Agency for Health Research and Quality from conveniently selected 178 nurses. Data were analyzed using SPSS Version 23 and statistics like frequency, percentage, mean, standard deviation and Mann Whitney U test was used for analysis.Results: This study found that only 13% of the respondents had high level of patient safety culture and 36% had average positive score to patient safety grade. Only the “feedback and communication of error” sub-dimension was the area of strength. Teamwork within unit and organizational learning and continuous development showed statistically significant difference (p